Challenging diagnosis of Wilson’s disease – a case report - Mansoor , Valeed Bin; Khan , Saad Yunus; Khan , Muhammad Arsalan; Khatoon, Shafat; Miraj, Muhammad Arqam; Syed, Fibhaa; Arif, Mohammad Ali (Journal of the Pakistan Medical Association, 2023)
Wilson’s disease is a rare inherited disorder of copper metabolism. If left untreated, it can turn into a multi systemic disease with copper deposition in the liver, brain, and other tissues. Diagnosis of Wilson’s is delayed in Pakistan by many years on average due to variable presentations. In adolescents, the initial signs are more likely to be neuropsychiatric. Here we present a case of Wilson’s disease that presented initially with hepatic symptoms and did not have signs specific to the disease such as Kayser-Fleischer rings. Our case was diagnosed to be Wilson’s Disease only on further investigations and subsequently the patient was treated with chelation therapy using D-Penicillamine.Wilson’s Disease should be kept in mind as a differential diagnosis in adolescent patients that present with unexplained acute liver failure and cytopenias without any neurological symptoms, as a missed diagnosis can prove to be fatal.